Biocarbonization Process for High Quality Energy Carriers: Techno-economics. (May 2017) - Kempegowda, Rajesh S.; Skreiberg, Øyvind; Tran, Khanh-Quang
Abstract: This work deals with a process design and techno-economic analysis (TEA) of the enablement of biocarbonization processes for production of biocarbon, biocrude, biomethane, biofertilizer and heat. Three case scenarios are developed with high levels of integration: a) Biocarbonization process for maximized biocarbon and heat; b) Co-carbonization of algae and woody biomass for biocrude and biochar; and c) Combined co-carbonization and biochemical platform. The approach used here is the combination of process modelling and simulation. Depending on the market dynamics, yields of products can be optimized. Holistically, the proposed processes attempt to reduce solid residues, gaseous emissions and liquid effluents generated in the biocarbon value chain.